Treatment of Whiplash-Associated Disorders - Part I: Non-Invasive Interventions - Anne Conlin; Robert Teasell; Sanjit Bhogal; Keith Sequeira (Pain Research and Management)
BACKGROUND: A whiplash-associated disorder (WAD) is an injury due to an acceleration-deceleration mechanism at the neck. WAD represents a very common and costly condition, both economically and socially. In 1995, the Quebec Task Force published a report that contained evidence-based recommendations regarding the treatment of WAD based on studies completed before 1993 and consensus-based recommendations.